Picoscale Magnetoelasticity Governs Heterogeneous Magnetic Domains in a Noncentrosymmetric Ferromagnetic Weyl Semimetal. Issue 3 (1st February 2021) - Xu, Bochao; Franklin, Jacob; Jayakody, Amani; Yang, Hung‐Yu; Tafti, Fazel; Sochnikov, Ilya
Abstract: Magnetic Weyl semimetals are predicted to host emergent electromagnetic fields at heterogeneous strained phases or at the magnetic domain walls. Tunability and control of the topological and magnetic properties are crucial for revealing these phenomena, which are not well understood or fully realized yet. Here, a scanning superconducting quantum interference device microscope is used to image spontaneous magnetization and magnetic susceptibility of CeAlSi, a noncentrosymmetric ferromagnetic Weyl semimetal candidate. Large metastable domains are observed alongside stable ferromagnetic domains. The metastable domains most likely embody a type of frustrated or glassy magnetic phase, with excitations that may be of an emergent and exotic nature. Evidence is found that the heterogeneity of the two types of domains arises from magnetoelastic or magnetostriction effects. It is shown how these domains form, how they interact, and how they can be manipulated or stabilized with lattice strains estimated to be on picometer levels. This knowledge can be used in designing and fabricating devices made from CeAlSi and related materials for magnetic field sensing and magnetic memory applications. Abstract : Scanning microscopy based on quantum magnetic sensing reveals two types of magnetic domains in a ferromagnetic noncentrosymmetric Weyl semimetal. The domains are strained by internal magnetization and some are metastable. This discovery can guide future efforts in building quantum nanodevices that combine magnetism, topology, and strain.